Anti-TNF therapy in Jordan: a focus on severe infections and tuberculosis - Alawneh KM (Dove Medical Press, 2014)
Khaldoon M Alawneh,1 Mahmoud H Ayesh,1 Basheer Y Khassawneh,1 Salwa Shihadeh Saadeh,1 Mahmoud Smadi,2 Khaldoun Bashaireh31Department of Medicine, College of Medicine, King Abdullah University Hospital, 2College of Science, 3Department of Special Surgery, College of Medicine, King Abdullah University Hospital, Jordan University of Science and Technology, Irbid, JordanBackground: A high rate of infection has been reported in patients receiving treatment with anti-tumor necrosis factor (anti-TNF). This study describes the rate of and risk factors for serious infections in patients receiving anti-TNF agents in Jordan.Methods: This retrospective observational study was conducted at a large tertiary referral center in the north of Jordan. Between January 2006 and January 2012, 199 patients who received an anti-TNF agent (infliximab, adalimumab, or etanercept) were included. Patients received the anti-TNF treatment for rheumatoid arthritis, ankylosing spondylitis, inflammatory bowel disease, or other conditions. A serious infection was defined as any bacterial, viral, or fungal infection that required hospitalization, administration of appropriate intravenous antimicrobial therapy, and temporary withholding of anti-TNF treatment.Results: The mean duration of anti-TNF treatment was 26.2 months. Steroids were used in 29.1% of patients, while 54.8% were given additional immunosuppressant therapy (methotrexate or azathioprine). Only one anti-TNF agent was given in 70.4% of patients, while 29.6% received different anti-TNF agents for the duration of treatment. Serious infections were documented in 39 patients (19.6%), including respiratory tract infections (41%), urinary tract infections (30.8%), and skin infections (20.5%), and extrapulmonary tuberculosis in three patients (7.7%). Exposure to more than one anti-TNF agent was the only factor associated with a significant increase in the rate of infection (relative risk 1.9, 95% confidence interval 1.06–4.0, P=0.03).Conclusion: Serious infections, including tuberculosis, were a common problem in patients receiving anti-TNF agents, and exposure to more than one anti-TNF agent increased the risk of serious infection.Keywords: anti-tumor necrosis factor therapy, biologics, developing world, extra-pulmonary tuberculosis, immune mediated diseases